Laser-induced multiphoton dissociation branching ratios for H2+ and D2+ - Hua, J. J.; Esry, B. D. (My University, 2009)
The multiphoton dissociation branching ratios for H2+ and D2+ as a function of laser peak intensity and pulse length are investigated by solving the time-dependent Schrödinger equation in the Born-Oppenheimer approximation, neglecting nuclear rotation. An 800 nm laser pulse with peak intensities from 8×109 W/cm2 to 1014 W/cm2 and pulse lengths from 5 to 7.5 fs is used. We also investigate the viability of identifying zero-, one-, two-, and three-photon processes based only on the nuclear kinetic energy release spectrum, and check these identifications with a rigorous Floquet-like method.